Pathological characteristics and long-term prognosis of submucosal infiltrating carcinoma of the colon and rectum below 2 cm confirmed by endoscopic submucosal dissection: Prognosis & endoscopic submucosal dissection of carcinoma - Zhou, Jun; Ling, Tingsheng; Xiao, Jun; Zhang, Qide; Wang, Lei (Cellular and Molecular Biology, 2024)
The purpose of this study was to explore the correlation between additional surgery and the clinicopathological characteristics of colorectal cancer, as well as its impact on patient prognosis. A total of 119 patients with early colorectal cancer were selected and divided into an additional surgery group (28 cases) and a non-additional surgery group (91 cases). According to the tumor size, the patients were further divided into a large diameter group (54 cases, d≥1 cm and <2 cm) and a small diameter group (65 cases, d<1 cm). The clinical and pathological characteristics as well as the prognosis of the patients were statistically analyzed. The results showed that infiltration type, depth of infiltration, and tumor size were correlated with additional surgery (P<0.05). Infiltration type and depth of infiltration were closely related to additional surgery. Differentiation degree, infiltration type, and depth of infiltration were correlated with tumor diameter. Infiltration type was closely related to tumor size. Age, depth of infiltration, and tumor size were correlated with patient survival rates. Infiltration type and depth of infiltration were closely related to patient survival rate (P<0.05). They were independent risk factors affecting patient prognosis. The 5-year disease-free survival rates were 73.33% and 72.5%, respectively, with no statistically significant difference. Infiltration type and depth of infiltration were independent risk factors for recurrence in colorectal cancer patients, while depth of infiltration was an independent risk factor for the 5-year survival rate after surgery. They can be used to predict the prognosis of colorectal cancer and guide clinical treatment as a supplement to the traditional staging of colorectal cancer.